Comparative Analysis Without and With Sensitivity Encoding (SENSE) on Signal to Noise Ratio (SNR) and Scan Time of Axial T2 Flair MRI Brain - Etikasari, Diah Ranu; Muhaimin, Muhaimin; Fajarini, Eunike Serfina (Sarana Ilmu Indonesia (salnesia), 2024)
T2 FLAIR has a long scanning time, because T2 FLAIR has additional TI (Time of Inversion) so patients feel uncomfortable. The SENSE produces image quality, namely contrast and spatial resolution, which is the same as standard image reconstruction, but the scan time required is only half of the standard scan time. This research aimed to determined the difference between SENSE and non-SENSE techniques in axial T2 FLAIR MRI Brain on SNR values and scan time. This study used 16 samples from all patients with T2 FLAIR axial MRI brain at Gambiran Hospital using SENSE and non-SENSE techniques. The results of the image were evaluated by quantitative method, by giving ROI (Region of Interest) to the cerebral cortex, basal ganglia, thalamus and noise background, then the signal intensity obtained from the organ image and the standard deviation (SD) of the background of the image was calculated by dividing the average signal of the measured area by SD at the noise to obtain the SNR value. The results of the SNR value were analyzed by the Paired T-Test and tested with the SPSS version 25. There was a difference between the SENSE and non-SENSE techniques in the axial T2 FLAIR MRI brain to the SNR value. This difference is because the T2 FLAIR non-SENSE does not experience the reduction in phase encoding lines needed to fill the image k-space on each coil element, a potential deficiency is met by the elimination of wrapping information that results in high image resolution spatial.